2015
DOI: 10.4309/jgi.2015.31.1
|View full text |Cite
|
Sign up to set email alerts
|

Gambling and Problem Behavior Among 14- to 16-Year-Old Boys and Girls in Finland

Abstract: The aim of this study is to examine the associations between problem behavior and gambling frequency among eighth- and ninth-grade boys and girls (N = 101,167). Data were obtained from the cross-sectional School Health Promotion Study. Outcome measures were adolescents' truancy, bullying, delinquency, and substance use. Polychotomous logistic regression analyses were used to study the relationship between gambling frequency and risk behaviors in a total sample, as well as separately for boys and girls. In 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Frequency was defined based on the type of game that occurred most often and recoded into two categories: 1) gambling weekly, and 2) gambling less often than weekly. We were interested in weekly gambling, because it is usually linked with disordered gambling [8] and other problem behaviours [14]. Those who participated on a weekly basis in lottery games only ( n = 48) were excluded because playing lotteries is generally viewed as a safe activity with little risk of harm [19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequency was defined based on the type of game that occurred most often and recoded into two categories: 1) gambling weekly, and 2) gambling less often than weekly. We were interested in weekly gambling, because it is usually linked with disordered gambling [8] and other problem behaviours [14]. Those who participated on a weekly basis in lottery games only ( n = 48) were excluded because playing lotteries is generally viewed as a safe activity with little risk of harm [19].…”
Section: Methodsmentioning
confidence: 99%
“…Both ARPG and weekly gambling may be associated with harmful behaviours such as smoking and alcohol misuse, as well as with depression [7]. Some studies have shown gender differences in associations between gambling, depression and risk-taking behaviours [14,15], men being more at risk. There is also evidence of a gender difference in Grade Point Averages (GPAs) in the Finnish education system, with girls more frequently scoring higher GPAs than boys [16].…”
Section: Introductionmentioning
confidence: 99%
“…More detailed information about questions regarding problem behaviour can be found elsewhere 34. Since problem behaviour indicator included measures with multiple behaviour types and responses, which were not necessarily identically scaled, latent classes were estimated.…”
Section: Methodsmentioning
confidence: 99%
“…Journal of studies on alcohol, 62(5), 706-712. Any solvent / drug use (Manning et al, 2017); Unhealthy alcohol consumption (Welte, Barnes, Wieczorek, Tidwell, & Parker, (2001); Smoking (Manning et al, 2017) Childhood Experience Close family member drinking / gambling as you were growing up, negative family environment (Grant et al, 2009); Experience of bullying (Räsänen, Lintonen, & Konu, 2015); Sexual abuse (Dion, Collin-Vézina, De La Sablonnière, Philippe-Labbé,, & Giffard, 2010); or Witnessing violence (Roberts et al, 2016) Mental Health Co-occurring mental health disorder; sought treatment for a mental health disorder (Lorains, Cowlishaw, & Thomas, 2011) Gambling Behavior Form specificity (matter what you gambled on), need for…”
Section: Accepted M Manuscriptmentioning
confidence: 99%